EFFECT OF THE TREATMENT OF IMPREGNATING TO VACUUM IN THE BREATHING OF MINIMALLY PROCESSED FRUITS (apple, strawberry, peach and watermelon) - GIRALDO G., Germán A. (Vitae, 2009)
There has been an outstanding growth in the consumption of barely processed food (BPF) in developed countries, particularly packed fruit and vegetables. The most common treatments for BPF are peeling, cutting, and sometimes enriching with nutritional components or products that ease processes such as breathing, which is a key factor in reducing the lifetime of both raw and barely processed vegetables. Gas concentration in the atmosphere, temperature, and other variables can affect the breathing process. Vacuum impregnation is one of the techniques that can be used in barely processed fruits in order to reduce O2 levels and in this fashion to incorporate anti-oxidants, preservatives, saccharine, acid, and other components in their structure. This is possible due to the porous skin that fruits have, which also makes possible small changes in fruit composition and thus to slow down the decaying rate that they may experience. The breathing index, influenced by vacuum impregnation using isotonic solutions in fruits, is regarded as a technological procedure that favors average life of fruits. This study analyzed the change of CO2 in samples of apple, strawberry, peach, and watermelon both not treated and treated with vacuum impregnation using isotonic solutions at 5 -10 ºC. In order to take gas samples, the experiment was carried out in a hermetic container connected to an automatic sampling system in a gas chromatograph. Samples were taken each 5 minutes during 2 hours, which was the estimated period for reaching atmosphere equilibrium. Results showed that vacuum impregnation reduces the breathing index in barely processed fruits up to 50%, depending on the kind of fruit that is being handled.